LPS-primed CD11b(+) leukocytes serve as an effective carrier of Shiga toxin 2 to cause hemolytic uremic syndrome in mice - Niu, Shuo (Sci Rep, 2018)
Shiga toxin (Stx)-induced hemolytic uremic syndrome (HUS) is a life-threatening complication associated with Stx-producing Escherichia coli infection. One critical barrier of understanding HUS is how Stx transports from infected intestine to kidney to cause HUS. Passive dissemination seems unlikely, while circulating blood cells have been debated to serve as the toxin carrier. Employing a murine model of Stx2-induced HUS with LPS priming (LPS-Stx2), we investigate how Stx causes HUS and identify possible toxin carrier. We show that peripheral white blood cells (WBC), but not other blood cells or cell-free plasma, carry Stx2 in LPS-Stx2-treated mice. The capability of WBC binding to Stx2 is confirmed in brief ex vivo Stx2 incubation, and adoptively transferring these Stx2-bound WBC into mice induces HUS. Cell separation further identifies a subpopulation in the CD11b(+) myeloid leukocytes not the CD11b(−) lymphocytes group act as the toxin carrier, which captures Stx2 upon exposure and delivers the toxin in vivo. Interestingly, LPS-induced inflammation significantly augments these leukocytes for binding to Stx2 and enhances HUS toxicity. Our results demonstrate that a specific fraction of circulating leukocytes carry Stx2 and cause HUS in vivo, and that LPS priming enhances the carrier capacity and aggravates organ damage.